A Study on the Content Analysis of 5th Grade English Textbook in Punjab, Pakistan - Muhammad Anwar; Rashid Mustafa; Dr. Javed Mustafa (Research Journal of Psychology, 2024)
This evaluative study was conducted to analyze the contents of fifth Grade English textbook published by the Punjab Textbook Board. Evaluation of the textbook was done by following Evaluation Criteria presented by Cunnings worth. Evaluation was done through content analysis. Aim of this research was to evaluate strengths and weaknesses regarding its alignment with educational standard. The evaluation identifies three primary weaknesses: inconsistency with Grade five learning levels, complex language structures that may hinder comprehension of fundamental concepts, and limited alignment of reading activities with the four foundational language skills (listening, speaking, reading, and writing). The study also explored decrease students’ motivation and learning outcomes due to vocabulary and grammar structures that exceed the cognitive abilities of typical Grade five learners. This study provides insights for educators and textbook developers to revisit the textbooks and inculcate the materials for enhancing English language instruction and the required language skills necessary for learners at primary level in Punjab. Key Words: Content Analysis, English Textbook, Fifth grade Level.